Homo covidus. Field observations - Lisitsin, Vasily; Lisitsina, Yana (project baikal, 2022)
The COVID-19 pandemic has had a significant impact on many areas of life and has changed some important processes, including educational ones. The crisis has affected almost all groups of the population, including young people who are just starting out in life: graduating from school, getting enrolled and studying in higher education. The article considers students’ reflections on the transformation of life, their comprehension of the changes.
Keywords: COVID-19 pandemic; higher education institutions; distance education; students; isolation